2019
DOI: 10.1073/pnas.1900163116
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic allostery-based molecular workings of kinase:peptide complexes

Abstract: A dense interplay between structure and dynamics underlies the working of proteins, especially enzymes. Protein kinases are molecular switches that are optimized for their regulation rather than catalytic turnover rates. Using long-simulations dynamic allostery analysis, this study describes an exploration of the dynamic kinase:peptide complex. We have used protein kinase A (PKA) as a model system as a generic prototype of the protein kinase superfamily of signaling enzymes. Our results explain the role of dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 63 publications
(77 reference statements)
0
57
0
Order By: Relevance
“…Dynamic allostery or entropically-driven allostery has been extensively studied in recent years, with its intriguing functional responses accompanied with the apparent lack of observable structural changes. [33][34][35][36][37][38][39][40][41][42] Dynamic allostery is an intrinsic property of enzymes and is intimately linked with catalysis. 34,39,42,43 In this study, we identified a key node embedded in an intricate and extensive allosteric network, which is remote to any ligand binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic allostery or entropically-driven allostery has been extensively studied in recent years, with its intriguing functional responses accompanied with the apparent lack of observable structural changes. [33][34][35][36][37][38][39][40][41][42] Dynamic allostery is an intrinsic property of enzymes and is intimately linked with catalysis. 34,39,42,43 In this study, we identified a key node embedded in an intricate and extensive allosteric network, which is remote to any ligand binding site.…”
Section: Discussionmentioning
confidence: 99%
“…This was expected based on the general globular characteristics of the CA domain and the post-translational nature of the considered modification, which is determined by the action of specific kinases on the folded protein. Exceptions were associated with the possible occurrence of molecular events related to the local unfolding action of kinases on CA flexible portions to be modified 44 , or the direct action of above-mentioned phosphorylating enzymes on degraded and/or unfolded molecular species 45 . In general, all phosphorylated amino acids occurred far away from the catalytic cavity.…”
Section: Fnlrellpk--qlgqyfryngslttppcyqsvlwtvfyrrsqismeqleklqgtlfsteementioning
confidence: 99%
“…Upon completion of our blinded analysis of the effects of these PTK inhibitors analogs on parasite maturation, we submitted our ranked list of the 10 most potent anti-malaria kinase inhibitors to our Eli Lilly collaborators for annotation with chemical identities and primary kinase target identification [36,[45][46][47][48][49][50]. Data from the annotation revealed that all potent inhibitors of P. falciparum egress at the segmenter stage as well as inhibitors of diamide and o-vanadate induced band 3 tyrosine phosphorylation ( Fig 4B) display Syk tyrosine kinase inhibitory activity.…”
Section: Plos Onementioning
confidence: 99%